FIRM INNOVATIVENESS AND ENVIRONMENTAL DISCLOSURE: EVIDENCE FROM NIGERIAN MANUFACTURING FIRMS - Mubaraq Sanni; Lukman Adebayo Oke ABDULRAUF; Jamiu Alabere Abdulrasheed (Malete Journal of Accounting and Finance)
The persistent increase in economic activities of companies, specifically manufacturing companies in Nigeria, has resulted in high levels of outputs, energy consumption, air pollution, and materials used. Environmental disclosures of these issues has become a major concern to communities, employees, shareholders, and other stakeholders and these difficulties drive this study. This study therefore, investigates the effect of the innovativeness and environmental disclosure of all listed manufacturing companies in Nigeria. Specifically, the paper investigates the extent at which firms’ complexity influences environmental disclosure, and how technological infrastructures affect environmental disclosure. With Ex-post factor research design and population of seventy-six (76) listed manufacturing companies, this paper employed Krejcie and Morgan (1970), while 63 companies formed the sample size. However, due to in availability of data and inconsistent listing of the companies, only forty-nine (49) out of the companies were chosen as the sample size determination table spanning across seven (7) sectors. Findings revealed that firms’ complexity and technological infrastructure have negative significant effect on environmental disclosure. Thus, this study recommends that Nigeria Exchange Group (NGX) should establish policy and penalties for companies that have not been adequate disclose information about their firms operating segment and new asset acquisition